Determinants and Controls of Scientific Development
XV, 460 p.
Keywords: This book constitutes the outcome of an international conference held at the Otto-Mobes-Volkswirtschaftsschule, Graz-Stifting( Austria), from June 16 to 22, 1974. The conference was initiated by a project group working on determinants and controls of social science development at the In stitute for Advanced Studies and Scientific Research in Vienna and or ganized by the editors of this volume. It was held under the auspices of the Austrian Ministry of Science and Research. The main topics of the conference were those at the forefront of the 'state of argumentation' (to borrow from one of our contributors) in philosophy and sociology of science ever since the controversy between Thomas S. Kuhn and Sir Karl R. Popper has sharpened our awareness for the methodological and substantial presuppositions involved with questions of growth and development in science. Let us give two examples of those topics. The borderline between sociology of science and philo sophy of science has become more and more unclear; while the work of at least some philosophers of science comes to have an empirical flavour, sociologists of science are increasingly apt to include logical and methodo logical components of the research process as their objects of examina tion. Papers included in this volume testify to both tendencies.